Freshwater crab research in Costa Rica: past, present and future - Wehrtmann, Ingo S.; Magalhães, Célio (Revista de Biología Tropical, 2025)
Introduction: Freshwater crabs occur in tropical and subtropical regions around the world and are due to their large biomass an important component in ecosystem processes. In Central America, Panama and Costa Rica stand out for their high diversity with 17 and 15 of freshwater crab species, respectively. Objective: Here we present an analysis of the freshwater crab research in Costa Rica and provide suggestions for future research topics related to these macro-invertebrates. Methods: The analysis is based on publications dealing with freshwater crab research in Costa Rica. We included only publications that included specimens collected in Costa Rica; on the contrary, publications, which only mentioned freshwater crab species from Costa Rica were not included. Results: The number of publications increased especially during the last two decades, reaching a total of 35 contributions. The history of freshwater crab research in Costa Rica might be divided into the following three periods: (1) Period I: pre-1900, the discovery phase as the start of freshwater crab research by the description of the first species from Costa Rica; (2) Period II: 1900–2000 when, after a long intermission, taxonomic studies on the freshwater crab fauna were resumed; and (3) Period III: post-2000 characterized by initiating studies including the ecology and molecular phylogeny of freshwater crabs while continuing the biodiversity assessment of these decapods. Conclusions: Our knowledge about freshwater crabs in Costa Rica has increased considerably, especially during the last decades; however, information about many aspects of the life history and ecology of these invertebrates remains fragmentary or simply absent. Future research areas might include studies about ecology and behavior, the impact of climate change and other stressors (e.g., pollution, deforestation, habitat loss, and invasive species) on the existing populations as well as their role as intermediate hosts for metacercariae of the trematode Paragonimus spp. Finally, we stress the need to maintain and continue the collection of freshwater crabs in the Universidad de Costa Rica.